IMPROVING GRADE V STUDENTS™ VOCABULARY ACHIEVEMENT THROUGH FLASH CARDS - Sitorus, Sabatini; Siregar, Masitowarni (TRANSFORM: Journal of English Language Teaching and Learning, 2013)
ABSTRACT This study attempts to increase students™ vocabulary achievement by using flash cards. The objective of the study is to investigate whether the using of flash card can improve students™ vocabulary achievement. This study conduct by applying Classroom Action Research which was carried out in two cycles in six meetings. The subject of this study of SD Negeri 174559 Siraituruk, Porsea which consisted of 34 students. For collecting data, the instruments used were quantitative (vocabulary test) and qualitative data (interview sheet, observation sheet, and diary notes. Based on the data, it was found that the mean of the second cycle (80, 44) is higher than the mean of first cycle (64, 85) and pre-test (44, 41).  Based on interview sheet, observation sheet and diary notes, it was found thee students were more active and more enthusiastic during the teaching learning process in the second cycle than the first one. It was concluded that teaching vocabulary by using  flash cards can improve the students™ vocabulary achievement.   Keywords : Flash Cards, Vocabulary, Action Research